Selection of drought-tolerant rice genotypes under cajuput (Melaleuca cajuputi subsp. cajuputi) agroforestry system - TARYONO TARYONO; SUPRIYANTA SUPRIYANTA; RANI AGUSTINA WULANDARI; NURMANSYAH NURMANSYAH; ERLINA AMBARWATI; I GUSTI KOMANG DANA ARSANA; VINA EKA ARISTYA; ARDIAN ELONARD PURBA; ALWA WIDI AISYA; TAUFAN ALAM (Society for Indonesian Biodiversity, 2023)
Abstract. Taryono, Supriyanta, Wulandari RA, Nurmansyah, Ambarwati E, Arsana IGKD, Aristya VE, Purba AE, Aisya AW, Alam T. 2023. Selection of drought-tolerant rice genotypes under cajuput (Melaleuca cajuputi subsp. cajuputi) agroforestry system. Biodiversitas 24: 4791-4802. Rice production can be increased by expanding rice cultivation area on agroforestry land. However, planting rice in agroforestry system, which is generally rainfed, might cause drought stress and eventually can reduce rice yields. The study aimed to select rice genotypes under drought stress conditions in a rainfed agroforestry system with cajuput or kayu putih (Melaleuca cajuputi subsp. cajuputi Powell). Ten promising rice lines and four control cultivars were grown during the dry season from March-July 2022 at the Menggoran Forest Management Resort, Playen Forest Section, Yogyakarta Forest Management, Indonesia. The observation was conducted on drought stress tolerance (sensitivity and recovery), molecular identification, and yield of rice cultivars. The results showed that G5 was the genotype with drought tolerance and had the best recovery compared to the other promising rice lines and control cultivars. The molecular identification of the 14 rice genotypes using 20 SSR markers detected 108 alleles with a PIC value of 0.707. The G5, G4, and G9 had higher yields than the control cultivars. The BLUE showed that the yield of G5, G4, and G9 were 6.59, 5.93 and 5.50 tons ha-1, respectively, while for BLUP by 6.45, 5.87 and 5.43 tons ha-1, respectively. Furthermore, there were four clusters consisting of cluster 1 (G9), cluster 2 (G7), cluster 3 (G5 and Inpago 12), and cluster 4 (Inpari 42, G6, Inpari 30 Ciherang Sub 1, Situ Bagendit, G3, G4, G10, G2, G1, and G8). The findings of this study recommend G4, G5, and G9 as promising rice lines which tolerant to drought stress under M. cajuputi agroforestry system and can be utilized in future plant breeding programs.